Participation in the Mubaligh Hijrah Program: Associations with Students’ Religious Character and Public Speaking Skills - Muhammad Fikri Noor Fadjri; Suwadi Suwadi (EDUKASI, 2026)
Religious character and public speaking skills are essential competencies in contemporary education. However, many students still face challenges in internalizing religious values and developing confidence in public communication. This study aimed to examine the associations between participation in the Mubaligh Hijrah Program and students’ religious character and public speaking skills. A quantitative approach using a cross-sectional survey design was employed. The participants consisted of 78 students from a private Islamic school in Yogyakarta, Indonesia, who had participated in the Mubaligh Hijrah Program. Data were collected using a Likert-scale questionnaire and analyzed through descriptive statistics and simple linear regression using RStudio and SPSS. Prior to analysis, assumption tests, including normality, linearity, and homoscedasticity, were conducted to ensure data suitability. The findings revealed significant positive associations between participation in the Mubaligh Hijrah Program and both students’ religious character and public speaking skills. Students with higher levels of participation tended to demonstrate stronger religious character and better public speaking skills. These findings underscore the potential value of community-based religious activities in supporting character education and communication skill development in Islamic schools.